Digitalization and Access to Household Credit in Indonesia: Pre- and-Post-COVID-19 Pandemic (2019 and 2021) - Puspita Sari, Cita; Sulistyaningrum, Eny (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objective: This study examines the effect of digitalization on access to household credit during the National Economic Recovery (PEN) program in Indonesia. Background Problems: Financial inclusion plays an important role in improving welfare and quality of life, accelerating economic growth, and alleviating poverty. Digitalization can affect financial inclusion through the transmission of mobile financial services, such as internet banking. Novelty: This study contributes to the literature on financial inclusion from the perspective of household credit. Research Method: This study uses the binomial log it model and data from the national socio-economic survey (SUSENAS) and statistics on village potential (PODES) from 2019 (before the pandemic) and 2021 (one year after the pandemic). Findings/Results: The results show that the average marginal effect of a household’s internet use was 1 percent higher than non-use before COVID-19. Meanwhile, after COVID-19, the marginal effect was 1.6 percent greater for households accessing credit through internet use than for those not using the internet. Furthermore, the probability of credit access is 4.6 percent higher for cell phone users than for non-users pre-COVID-19; meanwhile, post-COVID-19, the probability was 4.1 percent smaller than pre-COVID-19.The majority of households with access to credit are headed by males living in rural areas; they are married and working; they graduated from junior high school or above; and they are 30-59 years old. Conclusion: This study, by comparing 2019 to 2021, concludes that, as a result of the COVID-19 pandemic, digitalization accelerated access to household credit.